BRAFV600E 変異を認めたエナメル上皮癌の1例 - 長縄, 鋼亮; 村松, 泰徳; 江原, 雄一; 鵜飼, 哲; 渡邉, 一弘; 宮本, 侑果 (日本口腔外科学会雑誌, 2023)
The usual treatment for ameloblastic carcinoma is surgical resection. The effectiveness of radiotherapy and chemotherapy for the disease has not been determined, and few effective treatments are available for local recurrence and distant metastasis. Recently, molecular targeting using BRAFV600E inhibitors has attracted interest as a treatment for ameloblastoma and ameloblastic carcinoma.　Vemurafenib and dabrafenib are BRAF inhibitors that strongly and selectively inhibit BRAFV600E mutant kinases and exhibit anti-tumor effects. Although they are adapted for some malignant melanoma and non-small-cell lung cancer, they are expected to be effective as a molecular targeting therapy for ameloblastoma and ameloblastic carcinoma with BRAFV600E mutation.　We experienced a case of ameloblastic carcinoma that developed in the maxillary molar region and spread into the maxillary sinus. The patient was a 27-year-old male who presented to our hospital with the chief complaint of swelling and pain in the right maxillary molar region. Under the diagnosis of ameloblastic carcinoma, we performed a total maxillectomy, right neck dissection, and reconstruction with a rectus abdominis myocutaneous flap. Following the surgery, we conducted a BRAFV600E immunohistochemistry examination on the resected tumor and found that the solid and cystic tissues were positive for BRAF mutation.